2014
DOI: 10.1016/j.psychres.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met polymorphism does not moderate the effect of self-reported physical activity on depressive symptoms in midlife

Abstract: Background The brain-derived neurotrophic factor (BDNF) Val66Met single nucleotide polymorphism may be associated with clinical and subsyndromal depression, but physical activity improves mood and increases BDNF expression. Aims To examine whether the BDNF polymorphism moderates an effect of physical activity on depressive symptoms. Methods BDNF genotype, physical activity measured by the Paffenbarger Questionnaire, and depressive symptoms using the Center for Epidemiology Depression Scale (CES-D) were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
2
21
1
Order By: Relevance
“…Interestingly, this interaction between PA and the BDNF gene has not emerged with respect to depression outcomes. Despite one study in adolescent girls showing that PA was associated with fewer depressive symptoms for Met carriers (Mata et al 2010), more recent larger-scale studies (N >1,000) of depressive symptoms in both adolescents and adults have failed to replicate this effect (Gujral et al 2014, Stavrakakis et al 2013. These results suggest that the interaction between BDNF (or other genes) and PA may depend on the phenotype of interest, with cognitive outcomes showing different patterns than mood outcomes.…”
Section: Interactions Between Physical Activity and Gene Polymorphismsmentioning
confidence: 86%
“…Interestingly, this interaction between PA and the BDNF gene has not emerged with respect to depression outcomes. Despite one study in adolescent girls showing that PA was associated with fewer depressive symptoms for Met carriers (Mata et al 2010), more recent larger-scale studies (N >1,000) of depressive symptoms in both adolescents and adults have failed to replicate this effect (Gujral et al 2014, Stavrakakis et al 2013. These results suggest that the interaction between BDNF (or other genes) and PA may depend on the phenotype of interest, with cognitive outcomes showing different patterns than mood outcomes.…”
Section: Interactions Between Physical Activity and Gene Polymorphismsmentioning
confidence: 86%
“…However, the behavioral benefits vary in different subjects, suggesting that different factors may interact to produce distinct consequences. Indeed, some studies have addressed whether the BDNF Val66Met polymorphism moderates the response to exercise in human, producing mixed and inconclusive results, probably depending on the ethnic group, gender, age, and type and frequency of the exercise considered (Brown et al, 2014;Gujral et al, 2014;Hopkins et al, 2012;Lemos et al, 2016;Mata et al, 2010;Nascimento et al, 2015).…”
Section: Physical Exercise-induced Reduction Of Body Weight Gainmentioning
confidence: 99%
“…Val66Met SNP is associated with increased susceptibility to cognitive deficits and neuropsychiatric disorders Hariri et al, 2003;Lim et al, 2014;Notaras et al, 2015;Verhagen et al, 2010). Despite the strong evidence that exercise increases BDNF expression, only a few human studies have been conducted to address the potential role of Val66Met SNP in moderating exercise response, showing inconclusive results, probably due to confounding factors (Brown et al, 2014;Gujral et al, 2014;Hopkins et al, 2012;Lemos et al, 2016;Mata et al, 2010;Nascimento et al, 2015). Animal models may offer a useful tool to better address such question in a well-controlled environment and genetic setting.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that young adults with at least one 5-HTT L allele showed greater reductions in depressive symptoms after a 5-week exercise intervention [10]. In contrast, a recent cross-sectional study in middle-aged adults found that the BDNF Val66Met polymorphism did not moderate the relationship between self-reported physical activity and depressive symptoms [11]. This question has not been investigated in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that men and women not only differ in their risk for depression and vulnerability to depression-related negative sequelae, but also in the associations of genotype with depression risk and response to depression treatment [16, 17]. Some studies have reported a sex difference on the relationship between PA and depressive symptoms, with the effect being found exclusively or to a greater extent in either men [e.g., 18] or women [e.g., 11]. A recent meta-analysis of randomized trials showed a stronger effect of exercise in men [19].…”
Section: Introductionmentioning
confidence: 99%